2011
DOI: 10.1104/pp.111.186775
|View full text |Cite
|
Sign up to set email alerts
|

The Function of RH22, a DEAD RNA Helicase, in the Biogenesis of the 50S Ribosomal Subunits of Arabidopsis Chloroplasts    

Abstract: The chloroplast ribosome is a large and dynamic ribonucleoprotein machine that is composed of the 30S and 50S subunits. Although the components of the chloroplast ribosome have been identified in the last decade, the molecular mechanisms driving chloroplast ribosome biogenesis remain largely elusive. Here, we show that RNA helicase 22 (RH22), a putative DEAD RNA helicase, is involved in chloroplast ribosome assembly in Arabidopsis (Arabidopsis thaliana). A loss of RH22 was lethal, whereas a knockdown of RH22 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
77
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 79 publications
(105 reference statements)
4
77
0
Order By: Relevance
“…Probes were generated by PCR amplification of the relevant chloroplast sequences and labeled by the random priming method. The ribonuclease-protection assay of the RNA samples was performed as described by Chi et al (2012).…”
Section: Rna Coimmunoprecipitation Analysismentioning
confidence: 99%
“…Probes were generated by PCR amplification of the relevant chloroplast sequences and labeled by the random priming method. The ribonuclease-protection assay of the RNA samples was performed as described by Chi et al (2012).…”
Section: Rna Coimmunoprecipitation Analysismentioning
confidence: 99%
“…Arabidopsis mutant nara12-1, with reduced accumulation of RH39, showed strongly reduced levels of the photosynthesis machinery due to inefficient translation elongation, most likely due to the loss of RH39-mediated defects in 23S rRNA maturation (formation of the hidden break) affecting the functional state of the ribosome (Nishimura et al, 2010). Complete loss of Arabidopsis RH22 resulted into embryo lethality, whereas reduced RH22 expression resulted in virescent seedlings in which precursors of 23S and 4.5S rRNA (in the 50S particle) accumulated (Chi et al, 2012). It was concluded that RH22 facilitates the assembly of the 50S ribosomal subunit by interacting with ribosomal protein RPL24 and with the region of 23S rRNA encompassing the RPL24 binding site (Chi et al, 2012).…”
mentioning
confidence: 99%
“…Complete loss of Arabidopsis RH22 resulted into embryo lethality, whereas reduced RH22 expression resulted in virescent seedlings in which precursors of 23S and 4.5S rRNA (in the 50S particle) accumulated (Chi et al, 2012). It was concluded that RH22 facilitates the assembly of the 50S ribosomal subunit by interacting with ribosomal protein RPL24 and with the region of 23S rRNA encompassing the RPL24 binding site (Chi et al, 2012). Tobacco mutants with loss of the RH58 homolog (VDL helicase) showed pale-green and variegated leaves and abnormal roots and flowers, but no function was determined (Wang et al, 2000).…”
mentioning
confidence: 99%
“…In plants, DEADbox RNA helicases have been associated with diverse molecular functions such as siRNA-mediated gene silencing, premRNA splicing, chloroplast/mitochondrial intron splicing, nonsense-mediated mRNA decay, mRNA export, ribosome biogenesis and exon-junction complex functions. [11][12][13][14][15][16][17][18][19][20][21][22] Furthermore, it has been shown that these helicases play roles in Keywords: abiotic stress, Arabidopsis thaliana, DEAD-box RNA helicases, epigenetic gene silencing, nucleolus, RNAdirected DNA methylation Abbreviations: ABA, abscisic acid; STRS, STRESS RESPONSE SUPPRESSOR; RdDM, RNA-directed DNA methylation. various biological processes including abiotic stress responses.…”
mentioning
confidence: 99%